THE POTENTIAL OF NATURAL TOURISM VILLAGE OF THOUSAND GOA TOURISM HUMBANG HASUNDUTAN DISTRICT - Sepdwiyana Donargo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this study was to determine the natural tourism potential of a thousand caves as a natural tourist attraction in Humbang Hasundutan Regency. In this study using the method of observation, interviews, and qualitative methods. The results of the study are that a thousand caves have 800 to 1200 caves, the environmental conditions around a thousand caves are still natural, the uniqueness of a thousand caves is stunning carvings of stalactites and stalagmites, activities that can be done in a thousand caves are enjoying the beauty of flora and fauna, exploring caves, enjoying sunset panoramas , there are facilities in the form of toilets, photo spots, parking lots, and trekking areas. Based on the results of the research conducted, it was concluded that a thousand caves have the potential as a natural tourist attraction for the thousand cave tourism village, Humbang Hasundutan District.